Análisis financiero del Comercial Jessica Quezada Cia. Ltda. del Cantón Saraguro, período 2012-2013 - Cali González, Yessica Yhadira (2016)
The thesis entitled "FINANCIAL ANALYSIS OF COMMERCIAL JESSICA QUEZADA CIA. LTDA. CANTON SARAGURO, PERIOD 2012-2013 ", was held in order to choose the title of Engineer in Banking and Finance who was executed in accordance with the Regulation of Academic System of the National University of Loja to publicize the economic and financial development of the company as a basis for future decision making right with the administrative functioning of it for which it was developed based on both general and specific targets. Referring to the first specific goal: Make a vertical and horizontal analysis, to determine the financial structure of commercial Jessica Quezada Cia. Ltda. 2012-2013 period and determine the causes of the increases and decreases in different areas that comprise the financial statements of this entity, with the application of vertical analysis financial structure it knew where his present Current Assets 99.31 %, non-current assets of 0.69%, so it was determined that the company is at an appropriate level, considering that its current assets are maximized. The financing of the company's 88.43% is short-term debt and only self-financing ie 11.57% Heritage. The horizontal analysis determined an increase in its assets especially since an increase of 7.64%, in equity with a percentage of 96.42% and 1.96% minimum percentage of the liabilities of its indebtedness its suppliers. The second specific objective is to: Determine applicable financial indicators to measure the administrative and financial management, determining liquidity, activity, indebtedness and profitability, where indicators according to the nature of the economic activity of the company were applied inferring that account in 2013 with liquidity of $ 1.25, its activity of receivables 46 days and accounts payable 59 days, also has a debt of 88%, a very good level of profitability of 32%. The third specific objective is: Apply the Operating and Financial Leverage to determine the fixed and variable costs as a basis for the balance point that will reveal the level of operations that the company, which was obtained as a result in 2013 has to generate an income level of $ 2,204,980.45 and an installed capacity of 71% to cover its costs and expenses and not obtain or loss, no gain. It concludes with the fourth goal with the preparation of the report of financial analysis in order to inform the directors of the company on the effectiveness and efficiency with which manages the resources of the organization, it will serve as a support for decision making to future